Tracking in-match movement demands using local positioning system in world-class men's ice hockey - Douglas, A. S.; Kennedy, C. R. (The Journal of Strength and Conditioning Research, 2020)
While the global positioning system has been used in field sports for a decade, local positioning systems are newly available in indoor sports for the tracking of velocity and distance during competition. World-class male ice hockey players (n = 20) were monitored during 5 international matches. Speed and distance outputs were analyzed to determine the differences between positions, periods, and in-shift demands. Defense had a difference between forwards at distances covered at very slow (p < 0.001), slow (p < 0.001), and moderate (p < 0.001) speed. Forwards were found to cover a greater distance at very fast speed (p = 0.001) and sprint speed (p < 0.001). Defense had a decrease in skating distance at very fast (p < 0.001) and sprint skating speeds (p = 0.02). Forwards had an increase in very slow skating (p = 0.02) and a decrease in sprint skating distance (p = 0.02). Game situational differences were found for defense and forwards in average speeds for defense (p < 0.001) and forwards (p < 0.001). Local positioning systems data have the potential to accurately inform coaches of the position-specific demands of game situations and the training needs by position. Specifically, forwards performed more high-intensity skating than defensemen, whereas powerplay and penalty kill situations offered specific demands for the 2 positional groups. Finally, the intensity of skating was reduced in the third period for both defensemen and forwards. Further research can evaluate whether this is related to tactical decisions, or the metabolic cost of ice hockey.